The Effect of Expansion of Coverage and Employers’ Compliance on Pension Fund: A Case Study of SSNIT Teshie-Nungua Branch - Ofori, E.M. (University of Ghana, 2019)
The main purpose of the study was to examine the effect of expansion of coverage and employers’ compliance on pension fund. The study employed the convenience sampling design and sampled 150 Employers on the SSNIT scheme and 50 Staff of SSNIT for data collection purposes. The data was analyzed with the Statistical Package for Social Sciences. On the level of employers’ compliance, it was identified that employers pay their workers’ contributions regularly by the deadline for prudent investment of the pension fund and also, there has been a decrease in the non-compliance of workers’ contributions payment by employers due to enforcement of the compliance law. However, most of the employers have never faced a penalty on delayed payment of workers’ contributions. The overall level of compliance by the employers was noted to be high. The leading causes of employers’ compliance on pension’s scheme were observed to be the idea of retaining employees and stringent penalty rates. Other causes such as financial security in the future and legal obligations attached to pension scheme compliance were added by the employers. With references to the effects of employers’ compliance on pensions, the study noted that there has been an increase in pension funds and meeting investment expectations of pension funds. Nevertheless, the pension funds were not properly invested. In addition, the staff members were of the view that they achieved most pension fund goals, and SSNIT mostly benefited from the expansion of coverage. The overall rating of the success of the pension fund, which results from expansion of the scheme was considered good by the staff members. Based on the results of the study the following recommendations are worth considering. Since pension funds were not invested promptly and does not yield required returns, it is recommended that the management of pension funds should establish a strong organizational structure and policy implementation, which will enhance their portfolio composition. A solid organizational structure will also influence the firms’ investment portfolio choice leading to improved investment returns. In addition, the study recommended that payment of contributions by employers should continue adhering to the set regulations. From the study findings, regulation was found to have a significant influence on payment of contributions by employers and hence, managers of the Trust should put more measures in place to ensure that they are compliant. To ensure timely payment of contributions by employers, and deal with misappropriations of pension funds and investment/assets, SSNIT authorities must ensure effective implementation of the penalties provided by the non-compliance law, regardless of their position, status, affiliation or origin. Pension Fund Administrator should be transparent in their dealings and accountable to their clients through regular update of the employees’ contributions status. The contributory pension scheme should be encouraged by its practitioners in the form of provision of adequate means of sensitization or interactions such as seminars to continually update employers and employees on the benefits of the pension scheme and its importance on life after retirement.
EMBA.
Keywords: Pension Fund; SSNIT; Teshie-Nungua